The Influence of Marketing Competence on the Digital Online Garage Sale Community and Their Implications on Capital Investment Decisions (Case Study on the Development Business of the West Java Chamber of Commerce and Industry in Bandung) - Hendiarto, R. Susanto; Nurfalah, Ikhsan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Capital investment decisions, a case study on the West Java Kadin fostered business in Bandung. The research method applied is in the form of a descriptive analytical survey method, while the sample used is 32 respondents. The variables studied from each respondent are marketing competence, the Digital Online Garage Sale community, and capital investment decisions. The type of data collected is primary data. The results show that marketing competence has an effect on the Digital Online Garage Sale community. And the Digital Online Garage Sale community influences capital investment decisions. The object of this research is the sample of respondents used is still limited to the business assisted by the West Java Chamber of Commerce in Bandung, therefore further research is necessary based on more varied sampling with a longer duration, in order to obtain generalizable results.